The reenchantment of Digital Image: "Commercial Cuts" by Daniel Martínez through the "proposals" by Italo Calvino - del Pozo Ortea, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
This article engages with Daniel Martinez's Commercial Cuts, a video animation of the homonymous book of poems by the Spanish writer Javier Moreno. Commercial Cuts, I will discuss, is a videopoetic narrative on the mythical promise of salvation exercised by our world of adverstising. Following Italo Calvino's memos, and featuring the photograms from Martinez's narrative, I will discuss how this narrative ultimately emerges as a visual poetics that defends a recuperated mythical impulse of continuity for the contemporary visual regime. With it, it manages to overcome one of main blind spots of postmodernity: the negation of the mythical perspective.